F-squares based optimal designs for reduced cubic canonical models in four components. (2017) - Husain, Bushra; Sharma, Sanghmitra
Aggarwal et al. (2008) presented optimal orthogonal designs in two blocks based on F-squares for Darroch and Waller's quadratic mixture model in four components, while for Becker's and K-model, they presented their results in 2013. In this paper, we have constructed D-, A- and E-optimal designs in two blocks based on F-squares for new models called reduced cubic canonical model Forms I and II in four components when two component proportions are at the same level. Several criteria associated with the information matrix and eigenvalues for the designs are examined to infer characteristics in optimality. Conditions required for orthogonality are given for the reduced cubic canonical model Forms I and II.